Comparison of the clinical characteristics of diabetes mellitus diagnosed using fasting plasma glucose and haemoglobin A1c: The 2011 Korea National Health and Nutrition Examination Survey. (March 2016) - Hong, Sangmo; Kang, Jun Goo; Kim, Chul Sik; Lee, Seong Jin; Lee, Chang Beom; Ihm, Sung-Hee
Highlights: Among diabetic medications naïve subjects, the prevalence of diabetes was about 2.5% using the FPG criteria, 3.3% using the HbA1c criteria and only 1.6% met both criteria. The subjects with diabetes by the HbA1c criteria were older than the subjects with diabetes by the FPG criteria and the prevalence of diabetes by the HbA1c criteria only was three times more higher than that of daibetes by FPG only in the subjects older than 50 years old. HbA1c testing might be additional screening or diagnostic tool for older diabetic patients. Abstract: We compared the characteristics of a Korean adult population diagnosed with diabetes using only a fasting plasma glucose criterion or an HbA1c criterion. The single difference between these two groups was age. Further studies should be undertaken to clarify whether age-specific diagnostic criteria would be appropriate in Korean populations.